Effects of alkali dosage and silicate modulus on autogenous shrinkage of alkali-activated slag cement paste. (March 2021) - Chen, Weiwei; Li, Bo; Wang, Juan; Thom, Nicholas
Abstract: Autogenous shrinkage of alkali-activated slag cement (AASC) paste prepared with different levels of alkali dosage and silicate modulus (Ms ) is investigated. The results show that autogenous shrinkage of AASC paste increases at a decreasing rate with alkali dosage, which is attributed to enhanced capillary pore pressure and syneresis of C-A-S-H gels. Autogenous shrinkage of AASC paste with a constant alkali dosage increases as Ms increases from 0.5 to 1.0, followed with a reduction as Ms further increases to 2.0. Increasing Ms initially enhances the capillary pore pressure due to the enhanced reaction degree, and promotes the formation of saturated capillary pores and viscoelasticity, which facilitates the autogenous shrinkage of AASC paste. However, excessive silicate in the activator retards the internal moisture consumption, and subsequently decreases the autogenous shrinkage of AASC paste. Furthermore, increasing Ms can also intensify syneresis of C-A-S-H gels, contributing to the early-age autogenous shrinkage of AASC paste.